Bifurcation of Periodic Solution in Singular Perturbed Parameterized Ordinary Differential Equation (ODEs) - et. al., Khalid Frhan Fazea, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we study the bifurcation of the periodic solutions of the singularly perturbed parameterized differential equation(ODEs) of the form where is a bifurcation parameter and is a perturbed parameter, Our study focuses on Poincare map as a periodic solution of such ODEs. We have discussed and study the basic types of bifurcation in ODE that is saddle node, transcritical, pitchfork, and Hopf bifurcation.